Performance of upland sown direct seeded rice varieties grown in displaced soil under organic production system - Shahane, Amit A; Behera , UK (ORYZA-An International Journal of Rice, 2023)
The field experiment was conducted at Instructional Farm of College of Agriculture (CAU-I), Kyrdemkulai, Meghalaya in kharif season of 2021. The objective of experiment was to study performance of upland rice varieties (XRA 77922, XRA 87925, XRA 87928, XRA 752PJ6, XRA 37923 and XRA 38967) in displaced soil due to erosion and human traffic. All six rice varieties didn't show any significant different in growth and yield attributes; while all of them affected significantly due to abiotic stress arose due to soil erosion (shallow depth, high proportion of gravels, low water holding capacity and low soil fertility) leading to their sub-optimal growth and performance. The sub-optimal growth leads to susceptibility of rice varieties to blast disease, higher weed population and their flushes as well as termite infestation. The low fertility percentage of panicle (44.1 to 44.4 %), 25.3 to 28.0 (no.) filled spikelets, 212 to 221 tillers /m2, 22.7 to 25.7 g/m2 dry matter at 60 days after sowing, poor vegetative growth and drying of leaves towards the flowering and grain filling stage and grain and straw yield of 184.3-188.7 kg/ha to 671.3-676.0kg/ha showed the effect above mentioned stresses. The soil erosion is regular phenomenon in state and making field clear for upland cultivation increase the chances of soil erosion and fertility losses. This urge the need for additional effort along with crop management practices to enhance adoption of upland direct seeded rice and improvement in rice productivity by growing of new high yielding varieties in state and harvesting the genotype x environment positive interaction.